Screening of non‐steroidal anti‐inflammatory drugs for inhibitory effects on the activities of six UDP‐glucuronosyltransferases (UGT1A1, 1A3, 1A4, 1A6, 1A9 and 2B7) using LC‐MS/MS. (27th January 2015) - Joo, Jeongmin; Kim, Yang‐Weon; Wu, Zhexue; Shin, Jung‐Hoon; Lee, Boram; Shon, Jong Cheol; Lee, Eun Young; Phuc, Nguyen Minh; Liu, Kwang‐Hyeon
Abstract Non‐steroidal anti‐inflammatory drugs (NSAIDs) are used widely to relieve pain and to decrease inflammation. Several clinical studies have reported that NSAIDs inhibit uridine 5′‐diphospho‐glucuronosyltransferase (UGT) enzymes. Therefore, the study evaluated the inhibitory potential of 15 NSAIDs on the activities of six UGT isoforms (i.e. UGT1A1, 1A3, 1A4, 1A6, 1A9 and 2B7) in human liver microsomes (HLMs). Among the 15 NSAIDs tested here, mefenamic acid and diclofenac inhibited all UGTs tested in this study. Piroxicam and niflumic acid inhibited UGT1A9 activity (IC50 = 73.8 μm and 0.38 μm, respectively) and naproxen selectively inhibited UGT2B7 activity (IC50 = 53.1 μm), whereas it did not inhibit the other UGTs tested (IC50 > 200 μm). Diflunisal inhibited the UGT1A1 (IC50 = 33.0 μm) and UGT1A9 (IC50 = 19.4 μm). Acetaminophen, fenoprofen, ibuprofen, ketoprofen, meloxicam, phenylbutazone, salicylic acid and sulindac showed negligible inhibitory effects on the six UGTs (IC50 > 100 μm). These results suggest that some NSAIDs have the potential to inhibit UGTs in vitro. Copyright © 2014 John Wiley & Sons, Ltd.